3D printed piezoelectric energy harvesters - Zhou, Xinran (Nanyang Technological University, 2023)
The fast development of wearable electronic systems requires a sustainable energy source that can harvest energy from the ambient environment and does not require frequent charging. Mechanical energy is good energy source for wearable electronics energy harvesting because it is the most abundant energy source from environment, without the limitation of time and weather. To harvest mechanical energy, various mechanisms can be used, including piezoelectric, triboelectric, and electromagnetic induction effects, amongst which the piezoelectric energy harvester is a promising candidate due to its inherent polarization for stable performance. In recent years, flexible and stretchable piezoelectric energy harvesters are gaining interests for wearable electronics application, largely attributed to the increasing need of customized structure and integrated fabrication processes that can be achieved by 3D printing. The aim of this thesis is to study the 3D printing of piezoelectric materials and the 3D printed structure-enabled properties for wearable piezoelectric energy harvesters and sensors. The stretchability of the 3D printed piezoelectric energy harvester is realized both intrinsically with 3D printable elastomer matrix and extrinsically with 3D printed modified kirigami structure. For the intrinsically stretchable piezoelectric energy harvester, digital light projection (DLP) 3D printing is used to print the composite of two photocurable monomers and piezoelectric ceramic nanoparticles, followed by direct-write 3D printed stretchable electrodes. In this way, the first all-3D printed stretchable piezoelectric energy harvester was fabricated, and 434% stretchability can be achieved with relatively stable compression output voltage and sensitivity. For the extrinsically stretchable piezoelectric energy harvester, piezoelectric composite and conductive electrodes are printed with direct-writing 3D printing technique in a modified kirigami structure that converts the out-of-plane bending under stretching of the typical kirigami structure to the in-plane tilting to enable the compression energy harvesting under stretching. Up to 300% overall tensile strain can be achieved without affecting the compressive output voltage. Apart from enabling stretchability, the energy harvesting mode can also be changed by 3D printed special structures, which can make the previously untapped bending deformation on a film device useful for energy harvesting. By introducing the auxetic structure, the bending deformation, which generates negligible stress in a film piezoelectric device, can be converted into two directions of in-plane stresses, which activate the 3-1 and 3-2 type of piezoelectric effects for energy harvesting. The bending output voltage is 8.3 times of the same device without the auxetic structure. Therefore, it can be used as a bending angle sensor, which has a higher sensitivity than the state-of-art self-powered bending angle sensors. The research outcomes provide a design platform for the 3D printing of piezoelectric energy harvesters, by piezoelectric 3D printing ink development, integrated 3D printing of both piezoelectric material and electrode, 3D printed structure-induced output enhancement, and 3D printed structure-induced new energy harvesting mode development.